Association of human papillomavirus type 16 long control region mutation and cervical cancer - Chamsai Pientong (2018)
© 2013 Pientong et al; licensee BioMed Central Ltd. Background: The variation of human papillomavirus (HPV) genes or HPV variants demonstrates different risks of cervical cancer. Mutation in the long control region (LCR) at YY1-motifs is one of the mechanisms for enhancing viral oncogene expression during the course of cancer cell progression. In Thai women, cervical cancers are almost always associated with HPV16 variant sub-lineage Asian (HPV16As); however, the mechanism involved remains elusive. The aim of this study was to understand further the oncogenic potential of HPV16As. Methods: A total of 82 HPV16-positive specimens from Thai women were selected from formalin-fixed paraffin-embedded cervical tissues, and the full length E6 gene of each specimen was amplified and sequenced. LCRs of the HPV16As-positive cases were amplified and sequenced to analyze their polymorphisms. Transcriptional activities of the HPV16As LCRs were then compared with sub-lineage European (EUR), sub-lineage Asian-American 1 (AA1) and HPV16 prototype by insertion of the LCRs into the pGL3-Basic vector. Results: The HPV16 DNA sequences were classified as HPV16 prototype (18.3%), Asian (As, 61%), A sian American-1 (AA1, 8.5%), European (EUR, 7.3%), Asian African-2 (AFR2, 3.7%) and Java-135C (J135C, 1.2%). The prevalence of HPV16As was 30% in low-grade squamous intraepithelial lesion (LSIL), while that in high-grade squamous intraepithelial lesion (HSIL) and squamous cell cervical carcinoma (SCC) were 63.9% and 66.7%, respectively, which demonstrates a significant association of HPV16As with the disease severity. LCR polymorphisms from 43 HPV16As positive cases were analyzed by PCR-sequencing. Thirty-eight nucleotide variation positions spanned nucleotide positions 7157-82. Ten new mutations found in the HPV16As LCRs were located predominantly at the enhancer and proximal to the 3'-end of the early promoter. The LCRs of the common HPV16As, EUR and AA1 showed 5, 13 and 23-fold higher activity than the HPV16 prototype LCR, while those of the new nucleotide variations of As showed 19 (As-sv1) and 30 (As-sv14) -fold higher activity than the HPV16 prototype. Conclusions: HPV16As DNA sequence variation, especially at the proximal to early promoter in the LCR, enhances transcriptional activity. This could be one of the possible mechanisms for HPV16As-associated cervical cancer development.